2015
DOI: 10.4414/smw.2015.14137
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette: use and perceptions among French military nurses in 2013

Abstract: E-cigarette use among military nurses follows the trends observed in the general population in terms of prevalence and motives. E-cigarettes, which are seen as an attractive alternative to cigarettes, may contribute to a reduction in tobacco use among healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
4
2
0
Order By: Relevance
“…On the other hand, the prevalence of tobacco smoking recorded among students in the present survey was similar to that previously recorded among nursing students in Europe (34.3% of men and 27.5% of women) [27] and Greece (30.5% of men and 30.6% of women) [28] and in health professional students in the US (27.8% overall) [21]. A larger prevalence (40%) was recorded for French military nursing students and instructors [19]. The prevalence was lower among medical students from New York (3.9% smoking cigarettes and 2.1% smoking cigars) [20], among a population of mostly undergraduate students from Midwestern University (16.3%) [25] and among Italian post-graduate students attending the School of Public Health (26.2% of men and 16.2% of women) [24].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…On the other hand, the prevalence of tobacco smoking recorded among students in the present survey was similar to that previously recorded among nursing students in Europe (34.3% of men and 27.5% of women) [27] and Greece (30.5% of men and 30.6% of women) [28] and in health professional students in the US (27.8% overall) [21]. A larger prevalence (40%) was recorded for French military nursing students and instructors [19]. The prevalence was lower among medical students from New York (3.9% smoking cigarettes and 2.1% smoking cigars) [20], among a population of mostly undergraduate students from Midwestern University (16.3%) [25] and among Italian post-graduate students attending the School of Public Health (26.2% of men and 16.2% of women) [24].…”
Section: Discussionsupporting
confidence: 86%
“…The proportion of e-cigarette ever use reported by Italian nursing students (30.3%) was comparable to the proportion recorded in other academic settings, which ranged from 24 to 28% among American college students [21, 25] to 36% among French military nursing students [19]. Regarding current e-cigarette use, vapers were rare both among responders in the present study (2.1%) and among medical students from New York (1.6%) [20], while a much larger proportion was recorded among French military nursing students (25%) [19] and Arkansas health professional students (20.6%) [21].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…More recently, studies have indicated that medical and nursing students who currently smoke conventional tobacco are also more likely to use electronic cigarettes (e-cigarettes) and heated tobacco products [ 15–17 ], and less likely to reduce their conventional smoking [ 17 ]. There have been similar findings among French military nurses [ 18 ]. Yet, direct efforts to support smoking health professionals to quit are not only limited [ 19–22 ], the effectiveness of these interventions is lacking [ 23 ].…”
Section: Introductionsupporting
confidence: 63%